A ruthenium-based catalyst for hydrogen production by ammonia decomposition, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611221248.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]针对现有Ru基氨分解催化剂在低温活性、高空速适应性及活性组分稳定性方面仍需提升的问题,本发明提供一种用于氨分解制氢的钌基催化剂及其制备方法和应用
1. 本发明采用钡铝复合载体构筑钌基氨分解催化剂。Ba组分可提高载体碱性并调节Ru物种电子状态,Al组分有助于改善载体分散性、孔结构和热稳定性。二者协同能够为Ru物种提供适宜的锚定位点,避免单一Ba载体或单一 Al载体在活性与结构稳定性方面的不足。
Smart Images

Figure CN122955481A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ammonia decomposition for hydrogen production technology. More specifically, this invention relates to a ruthenium-based catalyst for ammonia decomposition for hydrogen production, its preparation method, and its application. Background Technology
[0002] Hydrogen, with its high energy density and clean conversion characteristics, is an important secondary energy source for building a low-carbon energy system. Ammonia, with a theoretical hydrogen storage capacity of 17.6 wt%, a high volumetric hydrogen density, mature production and transportation infrastructure, and relatively mild storage conditions, can serve as an important carrier for hydrogen storage, transportation, and on-site hydrogen supply. The efficient conversion of ammonia energy into hydrogen energy can be achieved through the decomposition reaction of ammonia into hydrogen and nitrogen.
[0003] Ammonia decomposition typically requires high temperatures to achieve high conversion rates, and the reaction process is also limited by factors such as strong adsorption of nitrogen species on the surface, coverage by hydrogen species, and sintering of active metal particles. Ru-based catalysts exhibit high intrinsic activity in ammonia decomposition, but their activity and stability depend on the particle size, dispersion state, electronic structure of Ru species, and their interaction with the support. Therefore, constructing support systems that can stabilize highly dispersed Ru species and improve the surface adsorption / desorption balance is an important direction for improving the catalytic performance of ammonia decomposition for hydrogen production.
[0004] Alkaline earth metal oxides or composite oxides possess strong basicity and electron-donating capabilities, which can influence the adsorption behavior of active metals for NH3, N, and H intermediates. Compared with alkaline earth metals such as Mg, Ca, and Sr, Ba exhibits stronger basicity and higher electron-donating ability, and is expected to enhance ammonia decomposition activity by regulating the basicity of the support surface, improving the electronic state of Ru species, and strengthening metal-support interactions. However, single Ba supports have insufficient specific surface area and structural stability, while single Al supports are insufficient to provide adequate basicity regulation. Constructing composite supports of Ba and Al, and combining them with liquid-phase reduction deposition to regulate the Ru species formation process, can provide a new preparation route for highly active ammonia decomposition catalysts. Summary of the Invention
[0005] To address the need for improvement in the low-temperature activity, high space velocity adaptability, and stability of active components of existing Ru-based ammonia decomposition catalysts, this invention provides a Ru-based catalyst for ammonia decomposition to hydrogen production, its preparation method, and its application.
[0006] To achieve these objectives and other advantages of the present invention, a ruthenium-based catalyst for hydrogen production from ammonia decomposition is provided, comprising a barium-aluminum composite support and an active component loaded thereon, said active component being ruthenium.
[0007] A method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described above includes the following steps: S1. Add barium salt, aluminum salt and precipitant to water and stir to dissolve to obtain precursor solution; S2. The precursor solution obtained in step S1 is subjected to a hydrothermal coprecipitation reaction. The resulting solid is washed, dried and calcined to obtain a barium-aluminum composite support. S3. Add barium-aluminum composite support, ruthenium precursor and alcohol solvent to the reactor, stir to form a suspension, and then carry out a stirring and heating reaction to obtain a ruthenium-based catalyst for ammonia decomposition to produce hydrogen.
[0008] Preferably, in S1, the barium salt is at least one of barium nitrate, barium chloride, and barium acetate; and the aluminum salt is at least one of aluminum nitrate nonahydrate, aluminum chloride, and aluminum sulfate.
[0009] Preferably, in S1, the barium salt contains Ba 2+ With Al in aluminum salts 3+ The molar ratio is 1:1 to 1:10, more preferably 1:1 to 1:3.
[0010] Preferably, in S1, the ratio of the total molar amount of barium and aluminum salt metal ions to the amount of water is 0.005~0.05 mol: 30~100 mL.
[0011] Preferably, in S1, the precipitant is urea, or a combination of urea and at least one of ammonium molybdate, sodium molybdate, and potassium molybdate; the molar ratio of the precipitant to the total metal ions of barium and aluminum salts is 12-16:1.
[0012] Preferably, in step S2, the hydrothermal coprecipitation reaction is carried out at a temperature of 120-160 °C for 12-24 h; the drying temperature is 50-80 °C for 8-16 h; and the calcination temperature is 400-600 °C for 2-6 h.
[0013] Preferably, in S3, the ruthenium precursor is at least one of ruthenium trichloride trihydrate, ruthenium acetate, and ruthenium nitrate; the mass ratio of the ruthenium precursor to the barium-aluminum composite carrier is 0.025~0.1:0.5~2.
[0014] Preferably, in step S3, the alcohol solvent is at least one of isopropanol, ethanol, n-butanol, and 2-butanol; the ratio of ruthenium precursor to alcohol solvent is 25-100 mg: 10-20 mL.
[0015] Preferably, in step S3, the stirring and heating reaction is carried out under the protection of nitrogen, argon or helium, with a gas pressure of 0.05~0.5 MPa, a stirring rate of 300~800 r / min, a reaction temperature of 180~220 ℃, and a reaction time of 2~4 h.
[0016] Application of a ruthenium-based catalyst as described above in ammonia decomposition for hydrogen production.
[0017] Application of a ruthenium-based catalyst prepared by the method described above in ammonia decomposition for hydrogen production.
[0018] Preferably, in the aforementioned application, the reaction temperature for hydrogen production from ammonia decomposition is 300–600 °C, and the space velocity is 30,000–75,000 mL·g. cat -1 ·h -1 .
[0019] The present invention has at least the following beneficial effects: 1. This invention employs a barium-aluminum composite support to construct a ruthenium-based ammonia decomposition catalyst. The Ba component enhances the basicity of the support and modulates the electronic state of Ru species, while the Al component helps improve the dispersibility, pore structure, and thermal stability of the support. The synergistic effect of both provides suitable anchoring sites for Ru species, avoiding the shortcomings in activity and structural stability of a single Ba or single Al support.
[0020] 2. This invention employs a hydrothermal coprecipitation method to prepare a barium-aluminum composite support. The reaction process is simple, the raw materials are readily available, and the conditions are mild. By controlling the Ba / Al molar ratio and the total concentration of metal ions, the support composition, pore structure, and surface alkalinity can be adjusted, thereby significantly affecting the low-temperature ammonia decomposition performance of the ruthenium-based catalyst.
[0021] 3. This invention employs an alcohol-based liquid-phase reduction deposition method to introduce Ru active components. The alcohol solvent acts as both a reaction medium and a mild reducing agent, promoting the gradual reduction of Ru precursors in the liquid phase and their deposition on the surface of the barium-aluminum composite support. This helps to inhibit the rapid aggregation of Ru species and enhances the interaction between Ru and the support.
[0022] 4. The Ru / Ba1Al3 catalyst prepared in this invention can be used at 30000 mL·g cat -1 ·h -1 It exhibits excellent low-temperature activity at space velocities, achieving a 99.2% NH3 conversion rate at 450 °C and near-complete decomposition above 500 °C; even with space velocities increased to 75000 mL·g cat -1 ·h -1 It can maintain an NH3 conversion rate of 83.0% at 450 ℃ and reach an NH3 conversion rate of 99.7% at 500 ℃, showing good potential for practical application.
[0023] Other advantages, objectives and features of the present invention will become apparent in part from the following description, and in part from those skilled in the art through study and practice of the invention. Attached Figure Description
[0024] Figure 1 The XRD patterns are of ruthenium-based catalysts with different Ba / Al molar ratios prepared in Examples 1-2 and Comparative Examples 4 and 6-7 of this invention. Figure 2 This is a SEM image of the Ru / Ba1Al3 catalyst prepared in Example 1 of the present invention; Figure 3 This is a TEM image of the Ru / Ba1Al3 catalyst prepared in Example 1 of the present invention; Figure 4 This is a stability test diagram of the Ru / Ba1Al3 catalyst prepared in Example 1 of the present invention. Detailed Implementation
[0025] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.
[0026] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.
[0027] Example 1 A method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition includes the following steps: S1, according to Ba 2+ :Al 3+ Barium nitrate and aluminum nitrate nonahydrate were weighed in a molar ratio of 1:3, and the total molar amount of metal ions was controlled to be 0.015 mol. They were then added to 50 mL of deionized water. Subsequently, 0.225 mol of urea was added as a precipitant, and the mixture was stirred at room temperature for 1 h to fully dissolve the metal salt and precipitant, thus obtaining the precursor solution. S2. The precursor solution obtained in step S1 is transferred to a hydrothermal reactor and crystallized at 140 °C for 18 h to obtain a white solid. S3. The white solid obtained in step S2 was filtered and washed with deionized water until the pH of the filtrate was about 7. Then it was dried at 60°C overnight and calcined at 500°C for 4 h in air atmosphere to obtain Ba1Al3 barium aluminum composite support. S4. Add 1 g of the Ba1Al3 barium aluminum composite support obtained in step S3, 50 mg of ruthenium trichloride trihydrate and 15 mL of isopropanol to the batch reactor, maintain the system pressure at 0.1 MPa under nitrogen atmosphere, and stir at 500 r / min to form a suspension. S5. The suspension obtained in step S4 is heated to 200 °C and kept for 3 h to allow the Ru precursor to undergo liquid-phase reduction in the isopropanol system and deposit on the surface of the Ba1Al3 barium aluminum composite support, thus obtaining a ruthenium-based catalyst named Ru / Ba1Al3.
[0028] Example 2 In this embodiment, Ba 2+ :Al 3+ The molar ratio of the feed was adjusted to 1:2; the remaining steps were the same as in Example 1, and a ruthenium-based catalyst was obtained, named Ru / Ba1Al2.
[0029] Example 3 In this embodiment, Ba 2+ :Al 3+ The molar ratio of the feed materials was adjusted to 1.5:1.5; the remaining steps were the same as in Example 1, resulting in a ruthenium-based catalyst named Ru / Ba. 1.5 Al 1.5 .
[0030] Example 4 In this embodiment, isopropanol is replaced with ethanol, and the remaining steps are the same as in Example 1.
[0031] Example 5 In this embodiment, isopropanol is replaced with n-butanol, and the remaining steps are the same as in Example 1.
[0032] Example 6 In this embodiment, isopropanol is replaced with 2-butanol, and the remaining steps are the same as in Example 1.
[0033] Comparative Example 1 In this comparative example, according to Mg 2+ :Al 3+ Magnesium nitrate and aluminum nitrate nonahydrate were weighed in a molar ratio of 1:3; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Mg1Al3.
[0034] Comparative Example 2 In this comparative example, according to Ca 2+ :Al 3+ Calcium nitrate and aluminum nitrate nonahydrate were weighed in a molar ratio of 1:3; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ca1Al3.
[0035] Comparative Example 3 In this comparative example, according to Sr 2+ :Al 3+ Strontium nitrate and aluminum nitrate nonahydrate were weighed in a molar ratio of 1:3; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Sr1Al3.
[0036] Comparative Example 4 In this comparative example, Ba 2+ :Al 3+The molar ratio of the feed was adjusted to 3:1; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba3Al1.
[0037] Comparative Example 5 In this comparative example, Ba 2+ :Al 3+ The molar ratio of the feed was adjusted to 2:1; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba2Al1.
[0038] Comparative Example 6 In this comparative example, Ba 2+ :Al 3+ The molar ratio of the feed was adjusted to 1:4; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba1Al4.
[0039] Comparative Example 7 In this comparative example, Ba 2+ :Al 3+ The molar ratio of the feed was adjusted to 1:5; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba1Al5.
[0040] Comparative Example 8 In this comparative example, Ba 2+ :Al 3+ The molar ratio of the feed was adjusted to 1:10; the remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba1Al. 10 .
[0041] Comparative Example 9 In this comparative example, no aluminum salt was added; only barium salt was used as the metal precursor to prepare the Ba support. The remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Ba.
[0042] Comparative Example 10 In this comparative example, no barium salt was added; only aluminum salt was used as the metal precursor to prepare the Al support. The remaining steps were the same as in Example 1, and the resulting catalyst was named Ru / Al.
[0043] Comparative Example 11 In this comparative example, the Ba1Al3 barium-aluminum composite support obtained in step S3 was potassium modified, and the resulting 5K-Ba1Al3 was used as the support. Specifically, 1 g of the Ba1Al3 barium-aluminum composite support obtained in step S3, 144 mg of potassium nitrate, and 15 mL of isopropanol were added to a round-bottom flask, sonicated for 1 h, and stirred for another 1 h to ensure that the potassium nitrate was fully contacted and dispersed with the barium-aluminum composite support. Subsequently, the solvent was removed by rotary evaporation at 50 °C to obtain a white powder sample. The obtained white powder sample was calcined in an air atmosphere, heated to 500 °C at a heating rate of 5 °C / min, and held for 2 h to obtain the potassium-modified barium-aluminum composite support, denoted as 5K-Ba1Al3. The remaining steps were the same as in Example 1, and the obtained catalyst was named Ru / 5K-Ba1Al3.
[0044] Comparative Example 12 In this comparative example, in step S4, potassium nitrate and ruthenium precursor were added to the reaction system simultaneously. Specifically, 1 g of the Ba1Al3 barium-aluminum composite support obtained in step S3, 50 mg of ruthenium trichloride trihydrate, 144 mg of potassium nitrate and 15 mL of isopropanol were added to the batch reactor. The system pressure was maintained at 0.1 MPa under a nitrogen atmosphere and the mixture was stirred at 500 r / min to form a suspension. The remaining steps were the same as in Example 1, and the resulting catalyst was named 5K-Ru / Ba1Al3.
[0045] Figure 1 The images show the XRD patterns of ruthenium-based catalysts with different Ba / Al molar ratios prepared in Examples 1-2 and Comparative Examples 4 and 6-7 of this invention; Figure 1 As can be seen, characteristic diffraction peaks of barium carbonate were observed in all samples, indicating that barium species in the obtained catalyst mainly exist in the barium carbonate crystalline phase. The diffraction peak intensities differed among samples with different Ba / Al molar ratios, indicating that adjusting the Ba / Al molar ratio can alter the crystal phase structure and crystallinity of the barium-aluminum composite support. Meanwhile, no obvious ruthenium-related crystalline phase diffraction peaks were detected in the samples, indicating that ruthenium species were well dispersed on the support. These results demonstrate that the preparation method described in this invention can obtain a barium-aluminum composite supported ruthenium-based catalyst with barium carbonate as the main crystalline phase and highly dispersed ruthenium species.
[0046] Catalyst structure and composition characterization: The Ru / Ba1Al3 catalyst obtained in Example 1 was characterized by scanning electron microscopy and transmission electron microscopy. The results are as follows: Figure 2 and Figure 3 As shown, the obtained barium-aluminum composite carrier forms a granular solid after hydrothermal co-precipitation and calcination, with Ru species loaded on the carrier surface.
[0047] Elemental analysis of samples with different Ba / Al molar ratios revealed that the actual Ba / Al molar ratio remained largely consistent with the feed ratio. When the Al proportion in the feed increased, the specific surface area and pore volume of the samples tended to increase, which is beneficial for improving the dispersion of active components and the contact efficiency of reactants. For example, the specific surface area of the Ru / Ba3Al1 sample was 36.9 m². 2 / g, pore volume 0.13 cm 3 The specific surface area of the Ru / Ba1Al3 sample was 42.1 m² / g. 2 / g, pore volume 0.17 cm 3 The specific surface area of the Ru / Ba1Al5 sample was 122.1 m² / g. 2 / g, pore volume 0.31 cm 3 / g,Ru / Ba1Al 10 The specific surface area of the sample is 143.6 m². 2 / g, pore volume 0.32cm 3 / g. The above results indicate that adjusting the Ba / Al molar ratio can effectively alter the texture properties of the barium-aluminum composite support.
[0048] Catalyst performance testing: The catalysts prepared in the examples and comparative examples were used for ammonia decomposition. The testing method was as follows: 0.1 g of catalyst was loaded into the isothermal zone of a fixed-bed reactor. Before the reaction, the catalyst was pretreated with H2 / Ar gas at 200 °C, then switched to NH3 feed, and activity testing was conducted at atmospheric pressure with a space velocity of 30000 mL·g⁻¹. cat -1 ·h -1 The composition of the outlet gas was analyzed using an online gas chromatograph equipped with a TCD detector, and the ammonia conversion rate was calculated according to the following formula: X NH3 = ([NH3] in - [NH3] out ) / [NH3] in × 100% Among them, X NH3 Indicates ammonia conversion rate, [NH3] in and [NH3] out These represent the inlet and outlet NH3 concentrations, respectively.
[0049] Table 1. Ammonia decomposition conversion rate (%) of alkaline earth metal composite supported catalysts of the same group As shown in Table 1, under the same M / Al feed design and liquid-phase reduction deposition conditions, the catalyst activity generally increases with the alkaline earth metal from Mg, Ca, Sr to Ba. The Ru / Ba1Al3 catalyst achieves an NH3 conversion rate of 78.2% at 400 °C and 99.2% at 450 °C, which is significantly higher than that of Ru / Mg1Al3, Ru / Ca1Al3, and Ru / Sr1Al3, indicating that the Ba component has a significant promoting effect on improving the low-temperature ammonia decomposition activity of the Ru-based catalyst.
[0050] Table 2 Effect of Ba / Al molar ratio on ammonia decomposition conversion rate (%) of ruthenium-based catalyst Table 2 shows that the low-temperature activity of Ru supported on a single Ba or Al support is relatively low, while the activity is significantly improved after constructing a composite support of Ba and Al. The Ba / Al molar ratio has a significant impact on the catalyst performance, with Ru / Ba1Al3 exhibiting the best or near-optimal ammonia decomposition activity in the 400–500 °C range. These results indicate that an appropriate amount of Al component can improve the structure and dispersion properties of the barium-based support, while an appropriate amount of Ba component provides the necessary basicity and electronic regulation capabilities.
[0051] Table 3 Ammonia conversion rate of Ru / Ba1Al3 catalyst at different space velocities / % Table 3 shows that increasing the space velocity shortens the contact time between the reactants and the catalyst, and the NH3 conversion rate decreases as expected at low temperatures. However, the Ru / Ba1Al3 catalyst at 75000 mL·g cat -1 ·h -1 The catalyst maintains an NH3 conversion rate of 83.0% at 450 °C and reaches 99.7% at 500 °C, indicating that it has good high space velocity adaptability.
[0052] Table 4 Effect of potassium addition method on ammonia decomposition conversion rate (%) of Ru / Ba1Al3 catalyst As shown in Table 4, in the barium-aluminum composite support system, regardless of whether potassium was introduced during the support synthesis stage or the catalyst synthesis process, the potassium-containing samples did not exhibit significantly better catalytic performance than Ru / Ba1Al3. This result indicates that the high activity of the catalyst in this invention mainly comes from the synergy between the Ba-Al composite support and the Ru species, and does not depend on additional potassium promoters.
[0053] Table 5. Effect of hydrogen-donating solvent type on ammonia decomposition conversion rate (%) of Ru / Ba1Al3 catalyst Examples 1 and 4-6 used isopropanol, ethanol, n-butanol, and 2-butanol as liquid-phase reduction deposition solvents to prepare ruthenium-based catalysts, respectively. Table 5 shows that in the high conversion range above 450 °C, the catalysts prepared with different alcohol reducing agents exhibit highly similar performance, indicating that ethanol, isopropanol, n-butanol, and 2-butanol can all be used as alcohol solvents and mild reducing agents in the system of this invention. Among them, isopropanol is widely available, reacts mildly, and is easy to operate, making it a preferred solvent.
[0054] In summary, the superior performance of the Ru / Ba1Al3 catalyst stems from the synergistic effect of the barium-aluminum composite support composition and the alcohol liquid-phase reduction deposition process. On one hand, the Ba component provides strong basicity and electronic regulation capabilities, which is beneficial for optimizing the adsorption / desorption balance of reaction intermediates at Ru active sites. On the other hand, the Al component improves the support texture and structural stability, enabling Ru species to be more uniformly dispersed and anchored on the composite support surface. The alcohol liquid-phase reduction deposition process can achieve the reduction and deposition of Ru precursors under mild conditions, which is beneficial for improving the dispersion of Ru species on the barium-aluminum composite support surface, thereby increasing the number of accessible active sites and improving catalytic stability.
[0055] Figure 4 This is a stability test diagram of the Ru / Ba1Al3 catalyst prepared in Example 1 of the present invention. The stability test shows that during continuous operation at 400℃ for 240 h, the NH3 conversion rate of the Ru / Ba1Al3 catalyst remained at 78%–81%, with almost no significant decrease. Multiple cycle experiments further demonstrate that after six repeated tests at 400℃ and 450℃, the catalytic activity remained almost unchanged. These results indicate that the catalyst of the present invention not only exhibits excellent initial activity under high-temperature ammonia decomposition conditions but also possesses good thermal stability and cycle durability.
[0056] Although embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details and illustrations shown and described herein.
Claims
1. A ruthenium-based catalyst for hydrogen production from ammonia decomposition, characterized in that, The ruthenium-based catalyst comprises a barium-aluminum composite support and an active component loaded thereon, wherein the active component is ruthenium.
2. A method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 1, characterized in that, Includes the following steps: S1. Add barium salt, aluminum salt and precipitant to water and stir to dissolve to obtain precursor solution; S2. The precursor solution obtained in step S1 is subjected to a hydrothermal coprecipitation reaction. The resulting solid is washed, dried and calcined to obtain a barium-aluminum composite support. S3. Add barium-aluminum composite support, ruthenium precursor and alcohol solvent to the reactor, stir to form a suspension, and then carry out a stirring and heating reaction to obtain a ruthenium-based catalyst for ammonia decomposition to produce hydrogen.
3. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S1, the barium salt is at least one of barium nitrate, barium chloride, and barium acetate; the aluminum salt is at least one of aluminum nitrate nonahydrate, aluminum chloride, and aluminum sulfate.
4. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S1, the Ba salt in the barium salt 2+ With Al in aluminum salts 3+ The molar ratio is 1:1 to 1:3; the ratio of the total molar amount of metal ions of barium and aluminum salts to the amount of water is 0.005 to 0.05 mol: 30 to 100 mL.
5. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S1, the precipitant is urea, or a combination of urea and at least one of ammonium molybdate, sodium molybdate, and potassium molybdate; the molar ratio of the precipitant to the total metal ions of barium and aluminum salts is 12-16:
1.
6. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S2, the hydrothermal coprecipitation reaction is carried out at a temperature of 120~160 ℃ for 12~24 h; the drying temperature is 50~80 ℃ for 8~16 h; and the calcination temperature is 400~600 ℃ for 2~6 h.
7. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S3, the ruthenium precursor is at least one of ruthenium trichloride trihydrate, ruthenium acetate, and ruthenium nitrate; the mass ratio of the ruthenium precursor to the barium-aluminum composite support is 0.025~0.1:0.5~2.
8. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In S3, the alcohol solvent is at least one of isopropanol, ethanol, n-butanol, and 2-butanol; the ratio of ruthenium precursor to alcohol solvent is 25~100 mg:10~20 mL.
9. The method for preparing a ruthenium-based catalyst for hydrogen production from ammonia decomposition as described in claim 2, characterized in that, In step S3, the stirring and heating reaction is carried out under the protection of nitrogen, argon or helium, with a gas pressure of 0.05~0.5 MPa, a stirring rate of 300~800 r / min, a reaction temperature of 180~220 ℃, and a reaction time of 2~4 h.
10. The application of a ruthenium-based catalyst as described in claim 1, or a ruthenium-based catalyst prepared by the preparation method according to any one of claims 2-9, in ammonia decomposition for hydrogen production, characterized in that, The reaction temperature for hydrogen production from ammonia decomposition is 300–600 °C, and the space velocity is 30,000–75,000 mL·g. cat -1 ·h -1 .